STUDY OF POPULATION DYNAMICS OF CHRYSOCORIS STOLLI WOLF (HETEROPTERA_PENTATOMIDAE SCUTELLERINAE) - P.K.SEHGAL; S.C.DHIMAN (International Journal of Pharma and Bio Sciences, 2016)
Population count was made on randomly selected ten plants. Weekly observation were taken and noted. On these basis monthly population was calculated and pooled in table –1.The count was made infield for two consecutive years, 2005 and2006.The data of table-2 depict that population built up of C.stolli starts in the month of late February or March on Cassia occidentalies plants and on Bajra . Pennisetum typhoid. The population goes on peak level on these plants during July to September when in nature abundant food supply is available. Further, data of frequency (F), abundance (A) and density (D) table – 50revealed that during 2005 at Saharanpur proper density varied from 1.35 to 4.15, frequency (F) was 30 to 100% percent and abundance was 1.42 to 4.08 during peak period of occurrence of bugs on Pennisetum typhoid’s (Bajra) crop. During 2006 density was 1.35 to 4.15, frequency 35 to 100% and abundance was 1.42 to 4.08.Calculation of frequency, density and abundance was carried using following formula. Density (D) = Total No. of individuals Total No of quadrates studied Frequency (F) = Number of quadrates in which the sp. Occurred Total No. of quadrates studied. Abundance (A) = Total No. of individuals Total No. of quadrates of occurrence.